2016
DOI: 10.1002/cam4.815
|View full text |Cite
|
Sign up to set email alerts
|

Response rates and durability of chemotherapy among 62 patients with metastatic Merkel cell carcinoma

Abstract: Cytotoxic chemotherapy is commonly used to treat advanced Merkel cell carcinoma (MCC). However, its efficacy in distant metastatic MCC patients is unclear, in part because most prior reports aggregated these patients with those receiving adjuvant chemotherapy and combined chemoradiation for whom prognosis and outcomes may differ. In this retrospective study, we analyzed detailed records from 62 patients with distant metastatic MCC treated with cytotoxic chemotherapy. Efficacy outcomes including response rate (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

8
197
6
12

Year Published

2016
2016
2021
2021

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 212 publications
(223 citation statements)
references
References 22 publications
8
197
6
12
Order By: Relevance
“…Despite these limitations, the results from this study are consistent with those of a recent retrospective analysis of patients with distant mMCC who received 2L chemotherapy, which reported an ORR of 23% and median PFS of 2 months [12]. Similar to the results reported here, the DOR was short (median DOR of 3.3 months [range: 0.2-7.4 months]).…”
Section: Discussionsupporting
confidence: 90%
See 2 more Smart Citations
“…Despite these limitations, the results from this study are consistent with those of a recent retrospective analysis of patients with distant mMCC who received 2L chemotherapy, which reported an ORR of 23% and median PFS of 2 months [12]. Similar to the results reported here, the DOR was short (median DOR of 3.3 months [range: 0.2-7.4 months]).…”
Section: Discussionsupporting
confidence: 90%
“…Treatments typically include platinum agents, such as carboplatin or cisplatin with or without etoposide or topotecan, and are associated with high toxicity [9,11]. Although MCC is generally considered a chemosensitive tumor, responses to chemotherapy in metastatic disease are often not durable: response rates in the secondline (2L) setting range from 23% in patients with known distant metastasis to 45% in patients with unclear (nodal and/or distant) sites of metastasis [12,13]. In the first-line (1L) or mostly 1L setting, response rates range from 53 to 61% [12][13][14][15][16][17].…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…This is in line with the fact that most AEs related to avelumab were low grade, consisting mostly of fatigue and infusion-related reaction. Taken together, this indicates that avelumab is well tolerated and that its safety profile was manageable, whereas previous studies in patients with mMCC treated with chemotherapy have shown high rates of significant toxicities [8][9][10][11].…”
Section: Discussionmentioning
confidence: 83%
“…Although virtually all patients are initially rendered free of detectable disease, roughly half of these patients will recur [95,96]. Once distant metastatic disease arises, cytotoxic chemotherapy leads to a response in >50% of cases, but the median time to progression is only 3 months and durable responses are exceedingly rare [97]. There is thus an urgent need for improved therapies.…”
Section: Treatment Of MCCmentioning
confidence: 99%